PERFORMANCE ANALYSIS OF A CAD/CAM-MATLAB/ SIMULINK INTERPRETER IN MILLING MACHINE APPLICATION - Jamaludin, Z.; Sudianto, A.; Mat Seman, N.; Othman, A.; Maharof, M.; Yahaya, S.H.; Patwari, A.U. (Journal of Advanced Manufacturing Technology (JAMT), 2023)
Geometrical accuracy and precision in machining process requires an efficient and accurate data conversion from the CAD of the part into the CAM machining details and subsequently the tracking control of the trajectories. For this purpose, a data exchange system via an interpreter design that integrates the CAD/CAM software and a milling machine position controller in MATLAB/Simulink platform was developed using the MATLAB graphical user interface module. The flexibility of the position control system of the milling table to accept alternative graphical input reference types was then enhanced. The G-codes of the standard three-dimensional geometrical CATIA-based CAD/CAM part production serve as input to the interpreter while the outputs were the respective x and y position data. These position data became the inputs to the cascade P/PI position controller of the milling machine. The experimental evaluations performed on the milling machine have proved the consistency in performance of the interpreter in tracking three different geometrical objects; a circular-shape, an oval-shape, and a random-curvy-shape. The root mean square of error (RMSE) values of 0.0057mm and 0.0064mm, 0.0063mm and 0.0064mm, and 0.0203mm and 0.0068mm for the x and y axes were measured respectively. The small position errors recorded testified the effectiveness of the interpreter design.